Digital Financial Services and Impact of M&A in the Banking Sector Performance: Case: Indonesian Fintech M&A on Banking Sectors - Eka Putra Budi Nugroho; Telisa Aulia Falianty (UNIVED Press, 2026)
This study examines the impact of bank acquisitions by financial technology (fintech) firms on the performance of conventional banks in Indonesia between 2017 and 2024. Employing a staggered Difference-in-Differences (DiD) approach with a double-robust estimator (did2s), the analysis focuses on four key indicators: market access (measured by the number of customer accounts), profitability (Net Interest Margin/NIM and Return on Assets/ROA), and operational efficiency (BOPO ratio). The findings reveal that fintech-led acquisitions significantly expanded customer accounts in the second year post-acquisition, indicating successful market reach. However, a sharp decline in NIM emerged in the first year, reflecting margin pressure. ROA showed initial improvement but diminished in subsequent years. No significant change was detected in the BOPO ratio, suggesting limited efficiency gains. These results indicate that digital integration yields immediate growth in customer base but slower improvements in financial metrics, shaped by integration challenges, regulatory factors, and competitive intensity. This study contributes to the Structure-Conduct-Performance (SCP) framework and Platform Economics by elucidating the complex dynamics of digital consolidation in Indonesia’s banking sector.